Large-scale genomic analysis reveals the distribution and diversity of type VI secretion systems in Escherichia coli - Kristina Nesporova; Bart Steemans; Sander K. Govers (mSystems)
ABSTRACT The type VI secretion system (T6SS) is a versatile nanomachine that injects effectors into target cells, playing a role in bacterial competition and virulence. While widespread in Gram-negative bacteria, T6SS prevalence varies across species and strains, and its distribution in Escherichia coli remains underexplored despite it being an important intestinal (IPEC) and extraintestinal (ExPEC) pathogen. Here, we examined the prevalence of T6SS subclasses (T6SSi) across 131,610 E. coli genomes, which we annotated for clinical relevance. T6SS genes were identified while focusing on the three subclasses present in E. coli: T6SSi1, T6SSi2, and T6SSi4b. Across phylogenetic groups, T6SSi1 was broadly present, while T6SSi2 showed associations with B1, B2, and G, and T6SSi4b was rare. T6SSi1 was primarily associated with IPEC, and T6SSi2 with ExPEC. Even clearer patterns emerged at the sequence type (ST) level. For example, both the most dominant ExPEC and IPEC ST (ST131 and ST11, respectively) displayed niche-specific trends, with non-complete T6SSs being more associated with humans. We also evaluated the co-occurrence of T6SSs with other virulence-associated genes (VAGs) and multidrug resistance (MDR). This analysis confirmed the association of T6SSi1 and T6SSi2 with IPEC- and ExPEC-associated VAGs, respectively, and revealed a negative correlation between complete T6SSi subclasses and MDR. Finally, we demonstrated how the presence of different T6SSs and VAGs can be used to examine and distinguish IPEC- and ExPEC-associated genomes. Together, our work provides a comprehensive overview of the diversity of T6SSs across E. coli, shedding more light on their potential contribution to pathogenicity in this species.IMPORTANCEOur study represents a large-scale analysis of T6SSs across one of the most comprehensive collections of E. coli genomes to date. In doing so, we updated several misconceptions on T6SSs distribution and other genomic properties of E. coli strains, which originated from smaller-scale studies and were subsequently extrapolated in the literature. This includes the prevalence and distribution of T6SSi subclasses across phylogenetic groups (e.g., T6SSi2 is not prevalent in phylogroup D), the association of specific virulence factors with IPEC and/or ExPEC (e.g., hemolysin A is more often associated with IPEC and not a typical ExPEC characteristic), and characteristics of pathogenic STs (e.g., ST131 displays distinct genomic properties based on its environmental niche). As such, this study not only advances our understanding of T6SS in E. coli but also serves as a valuable resource for future studies on the clinical relevance and distribution of other genetic elements.